Serial whole-brain magnetization transfer imaging in patients with relapsing-remitting multiple sclerosis at baseline and during treatment with interferon beta-1b. - Richert, N D; Ostuni, J L; Bash, C N; Duyn, J H; McFarland, H F; Frank, J A (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE To determine whether occult disease fluctuates with macroscopic lesions during the natural history of multiple sclerosis (MS) and whether therapeutic interventions affect occult disease, we performed serial monthly magnetization transfer (MT) imaging in patients with relapsing-remitting MS in a crossover trial with interferon beta-lb.METHODS Serial whole-brain magnetization transfer ratios (MTRs) in eight patients with relapsing-remitting MS and in four control subjects were plotted as normalized histograms, and MTR parameters were compared with contrast-enhancing lesions and bulk white matter lesion load.RESULTS In patients with relapsing-remitting MS, the histographic peak of 0.25+/-0.01 and the histographic mean of 0.21+/-0.01 were statistically lower than corresponding values in control subjects, in whom the histographic peak was 0.27+/-0.01 and the histographic mean was 0.23+/-0.01. When histograms (with MTRs ranging from 0.0 to 0.5) were analyzed by quartiles (quartile 1 to quartile 4) based on histographic area, voxels with low MTRs in quartile 1 (0 to 0.12) increased during the baseline period and corresponded to bulk white matter lesion load. Interferon beta-lb reduced enhancing lesions by 91% and mean bulk white matter lesion load by 15%, but had no effect on MTR in this patient cohort.CONCLUSION Occult disease in normal-appearing white matter of patients with relapsing-remitting MS measured by MTR parallels the waxing and waning pattern of enhancing lesions and bulk white matter lesion load during the baseline period. MTR is not altered by interferon beta-lb, which raises the possibility of ongoing disease in normal-appearing white matter (not detected by conventional MR sequences).